2022
DOI: 10.1039/d1cc05700f
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to ondansetron and alosetron inspire a versatile, flow photochemical method for indole synthesis

Abstract: An oxidative photocyclisation to indoles is described, that mirrors the Fischer indole synthesis but uses anilines in place of arylhydrazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Accordingly, we chose N -methylaniline ( 9 ) as a more readily available starting compound than 1-methyl-1-phenylhydrazine ( 3 ), surmising that condensation of 9 with 1,3-cyclohexanedione ( 2 ) would give enaminone 10 , which could be converted into the same ondansetron precursor ( 5 ) by oxidative cyclization. 11 During the course of our study, a comparable oxidative cyclization of 10 to 5 in a flow photochemical process was reported, 12 prompting us to shift our focus to the other three steps in the ondansetron synthesis. Herein we describe our improvements to the synthetic process of ondansetron by the development of continuous synthesis methods for the initial condensation noted above (step 1), the Mannich reaction (step 3), and substitution with 2-methylimidazole ( 8 ) (step 4).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Accordingly, we chose N -methylaniline ( 9 ) as a more readily available starting compound than 1-methyl-1-phenylhydrazine ( 3 ), surmising that condensation of 9 with 1,3-cyclohexanedione ( 2 ) would give enaminone 10 , which could be converted into the same ondansetron precursor ( 5 ) by oxidative cyclization. 11 During the course of our study, a comparable oxidative cyclization of 10 to 5 in a flow photochemical process was reported, 12 prompting us to shift our focus to the other three steps in the ondansetron synthesis. Herein we describe our improvements to the synthetic process of ondansetron by the development of continuous synthesis methods for the initial condensation noted above (step 1), the Mannich reaction (step 3), and substitution with 2-methylimidazole ( 8 ) (step 4).…”
Section: Introductionmentioning
confidence: 58%
“…The batch conditions previously described 12 were used as a starting point for our initial studies of the condensation step (step 1). We found that the reaction time of 16 hours in batch could be reduced to a 30 minute residence time in flow.…”
Section: Resultsmentioning
confidence: 99%
“…Tetrahydrocarbazol-4-ones are pivotal frameworks of many biologically active compounds, both natural and synthetic (Figure ). Furthermore, substituted tetrahydrocarbazol-4-ones, as the functionalized intermediates, are widely used in the total synthesis of natural alkaloids, drugs, and functional materials . A number of reliable methods for the preparation of tetrahydrocarbazol-4-one derivatives have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, Sun and David Harrowven described an oxidative photocyclisation of N -arylenaminones to indoles by continuous-flow technology under UV light (Scheme 1b). 9 To date, all these reports rely either on the use of transition-metal catalysis (iridium polypyridyl complexes) or on nonselective UV light.…”
Section: Introductionmentioning
confidence: 99%